(untitled) (Research, Society and Development, 2022)
The students with high abilities and giftedness, have characteristics associated with intelligence, high learning conditions in studies, so they need adequate work that allows their inclusion and enable learning adapted to their conditions. At first, the recognition of students with high abilities is the main factor that inserts the accomplishment of inclusion work. In this context, the objective of this study is to analyze how the recognition and inclusion of students with high skills occurs in the state public education network of Minas Gerais. The present research has an exploratory, descriptive, quanti-qualitative character. Being applied from a semi-structured questionnaire, online, through the Google Forms platform. Eighteen elementary school teachers from the state public network of Minas Gerais participated in the research. An informed consent form was entered for data collection and use. The results of the present study indicate the lack of discussions related to students with high abilities and giftedness, the difficulty and lack of adequate recognition and the implementation of inclusive work. In the practice of the school context, there is a lack of work aimed at the identification and progress of these students, which can in turn result in delays in learning and in the lack of appreciation of the student’s potential. However, the process of recognition and inclusion of the student with high skills is of great relevance, which presents a need for insertion, dialogue and implementation within regular education.